NLRP3 inflammasome activation and disruption of IRS-1/PI3K/AKT signaling: Potential mechanisms of arsenic-induced pancreatic beta cells dysfunction in rats - Yonglian Liu; Wenjuan Wang; Bing Liang; Zhonglan Zou; Aihua Zhang (Ecotoxicology and Environmental Safety)
Environmental exposure to arsenic is associated with significant health risks, including diabetogenic effects linked to pancreatic dysfunction. The NOD-like receptor protein 3 (NLRP3) inflammasome has been implicated in various metabolic abnormalities; however, its specific role in arsenic-induced pancreatic dysfunction remains insufficiently understood. This study aimed to elucidate the involvement and underlying mechanisms of the NLRP3 inflammasome in arsenic-induced pancreatic beta cells dysfunction through in vivo and in vitro models. In rat models, arsenic exposure was found to activate the NLRP3 inflammasome, as evidenced by pathomorphological changes and the expression of inflammasome activation markers. These pathological changes were accompanied by disruptions in the insulin signaling pathway, characterized by increased phosphorylation of insulin receptor substrate 1 (IRS-1) at Ser616, reduced expression of phosphatidylinositol 3-kinase (PI3K) and phosphorylated protein kinase B (AKT) at Ser473, and significant decreases in downstream targets, including the nuclear translocation of PDX-1, membrane translocation of glucose transporter 2 (GLUT2), and glucokinase (GCK) expression. In vitro, NaAsO2-treated INS-1 cells exhibited a dose-dependent reduction in glucose-stimulated insulin secretion. Furthermore, arsenic exposure in these cells activated the NLRP3 inflammasome, suppressed the IRS-1/PI3K/AKT signaling pathway, and downregulated insulin secretion regulatory molecules (PDX-1, GLUT2, and GCK). Notably, these arsenic-induced effects were reversed by MCC950, an NLRP3 inflammasome inhibitor, and Extendin-4, an agonist of the IRS-1/PI3K/AKT signaling pathway. Collectively, these findings demonstrate that NLRP3 inflammasome activation disrupts the IRS-1/PI3K/AKT signaling pathway, contributing to arsenic-induced pancreatic beta cells dysfunction in rats.